Analisis Pengetahuan Lingkungan Berbasis Kearifan Lokal pada Pola Pemupukan, Pergiliran Tanaman dan Kebersihan Ladang Masyarakat di Kabupaten Karo dan Kabupaten Deli Serdang - Ginting, Permata; Syarifuddin, Syarifuddin; Harahap, Fauziyah (Jurnal Pendidikan Biologi, 2016)
This type of research is ex post facto, the sampling technique used was stratified random sampling. This study aims to determine the level of environmental knowledge based on local wisdom on the pattern of fertilization, crop rotation and cleanliness of public fields in Karo and Deli Serdang. Data was collected using a questionnaire to calculate percentages, looking for differences in normal distribution of data using the formula Kolmogorov-Smirnov (K-S) and also for the homogeneity of the data used by the formula of environmental knowledge Levene. Based on the results of ANOVA test a significant difference to the level of public knowledge (F = 4.41; P = 0.035). The level of knowledge of the agricultural environment in the communities in Karo, 24.91 ± 5.74 (SB) was significantly higher than the level of environmental knowledge of farming communities in Deli Serdang 23.74 ± 6.56. Based on the Anova test results on the data level of knowledge of the agricultural environment in the communities in Karo and Deli Serdang found that the location of agricultural land significant effect on the level of knowledge society. Based on Tukey test results showed that the level of environmental knowledge of peasant farming, 28.42 ± 4.01 was significantly higher than the level of environmental knowledge of primary school students, 18.40 ± 4.46, and the level of environmental knowledge of junior high school students, 22.27 ± 4, 51 but did not differ significantly with the level of environmental knowledge of high school students, 28.47 ± 4.54. Based on the results of Anova test of the influence of a significant interaction between the location of the farm to the knowledge society in Deli Serdang (F = 68.829; P = 0.000), for Karo (F = 28.558; P = 0.000). Based on Tukey test results can be seen that there are differences in the environmental knowledge owned by farmers, high school students, junior high school students, elementary students in Karo and Deli Serdang is significantly different overall. Knowledge society in terms of fertilization, farming communities have chosen manure and compost as a fertilizer major to restore soil fertility, but can not be separated from chemical fertilizers. Chemical fertilizer given to plants to see its development. The community also has been farming in rotation and in the hygiene field, to eradicate the weeds are still using herbicides.